The U.S. – Poland Income Tax Treaty - Smiley, Stafford (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The article deals with the U.S. program of renegotiating all the U.S. income tax treaties including the 2013 tax treaty between the U.S. and Poland. The Author discusses reasons why almost a decade later, neither of these treaties has been ratified by the U.S. Senate.